2014
DOI: 10.1111/tpj.12521
|View full text |Cite
|
Sign up to set email alerts
|

A unique Ni2+ ‐dependent and methylglyoxal‐inducible rice glyoxalase I possesses a single active site and functions in abiotic stress response

Abstract: SUMMARYThe glyoxalase system constitutes the major pathway for the detoxification of metabolically produced cytotoxin methylglyoxal (MG) into a non-toxic metabolite D-lactate. Glyoxalase I (GLY I) is an evolutionarily conserved metalloenzyme requiring divalent metal ions for its activity: Zn 2+ in the case of eukaryotes or Ni 2+ for enzymes of prokaryotic origin. Plant GLY I proteins are part of a multimember family; however, not much is known about their physiological function, structure and metal dependency.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
118
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(137 citation statements)
references
References 55 publications
7
118
0
3
Order By: Relevance
“…Of the 41 genes found in that database (Table 2), 18 have been linked to various abiotic-stress responses in rice. They include PhyB (Liu J. et al, 2012), OsbZIP52 / RISBZ5 (Liu C. et al, 2012), OsETOL1 (Du et al, 2014), trehalose-6-phosphate synthase 1 ( OsTPS1 ; (Li H. W. et al, 2011), OsTZF1 (Jan et al, 2013), and sHSP17.7 (Sato and Yokoya, 2008) for drought; OsCIPK15 (Xiang et al, 2007), OsGAPC3 (Zhang et al, 2011), glyoxalase I ( OsGLYI-11.2 ; Mustafiz et al, 2014), Programmed cell death 5 ( OsPDCD5 ; Yang et al, 2013), OsPLDα1 (Shen et al, 2011) OsTPS1 (Li H. W. et al, 2011), and OsTZF1 (Jan et al, 2013), for salinity; OsbZIP52 / RISBZ5 (Liu C. et al, 2012) OsLti6b (Kim et al, 2007), OsTPS1 (Li H. W. et al, 2011), and v1 (Kusumi et al, 2011) for chilling; and ETHYLENE OVERPRODUCER 1-like ( OsETOL1 ) for tolerance to submergence (Du et al, 2014; Table 2). These findings indicate that our candidate genes are potentially involved in plant responses to abiotic stress (including drought) and suggest the possibility of crosstalk among related pathways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 41 genes found in that database (Table 2), 18 have been linked to various abiotic-stress responses in rice. They include PhyB (Liu J. et al, 2012), OsbZIP52 / RISBZ5 (Liu C. et al, 2012), OsETOL1 (Du et al, 2014), trehalose-6-phosphate synthase 1 ( OsTPS1 ; (Li H. W. et al, 2011), OsTZF1 (Jan et al, 2013), and sHSP17.7 (Sato and Yokoya, 2008) for drought; OsCIPK15 (Xiang et al, 2007), OsGAPC3 (Zhang et al, 2011), glyoxalase I ( OsGLYI-11.2 ; Mustafiz et al, 2014), Programmed cell death 5 ( OsPDCD5 ; Yang et al, 2013), OsPLDα1 (Shen et al, 2011) OsTPS1 (Li H. W. et al, 2011), and OsTZF1 (Jan et al, 2013), for salinity; OsbZIP52 / RISBZ5 (Liu C. et al, 2012) OsLti6b (Kim et al, 2007), OsTPS1 (Li H. W. et al, 2011), and v1 (Kusumi et al, 2011) for chilling; and ETHYLENE OVERPRODUCER 1-like ( OsETOL1 ) for tolerance to submergence (Du et al, 2014; Table 2). These findings indicate that our candidate genes are potentially involved in plant responses to abiotic stress (including drought) and suggest the possibility of crosstalk among related pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Many rice genes in pathways for carbohydrate, cell wall, lipid, and amino acid degradation are stimulated when the water supply is limited, thereby implying that plants use those metabolites and energy resulted from degradation pathways to tolerate stressful growing conditions. For example, a unique Ni 2+ -dependent and methylglyoxal-inducible GLY I functions in the response and adaptation of rice to abiotic stresses (Mustafiz et al, 2014). The phospholipase Dα (PLDα) mediates H(+)-ATPase activity and is involved in salt tolerance (Shen et al, 2011; see also Figure 6A, Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In bacteria Ni is present in several enzymes, including urease, glyoxalase-I, hydrogenases, some superoxide dismutases, carbon monoxide dehydrogenase and methyl-coenzyme M reductase (Ragsdale, 1998). Until recently urease was the only known Ni-containing enzyme in higher plants (Polacco et al, 2013), but Mustafiz et al (2014) reported that plant glyoxalase-I requires Ni for maximal activity. While glyoxalase-I appears to be activated by Ni in vitro (Mustafiz et al, 2014), in the absence of other proteins, Ni activation of urease requires three accessory proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently urease was the only known Ni-containing enzyme in higher plants (Polacco et al, 2013), but Mustafiz et al (2014) reported that plant glyoxalase-I requires Ni for maximal activity. While glyoxalase-I appears to be activated by Ni in vitro (Mustafiz et al, 2014), in the absence of other proteins, Ni activation of urease requires three accessory proteins. The assembly of the urease Ni metallocenter is not yet clearly understood (Carter et al, 2009; Witte, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The metal ion requirement of the GLYI enzyme was previously believed to be linked to its origin, with the prokaryotic GLYI being Ni 2+ -dependent enzymes and the eukaryotic GLYI being Zn 2+ -dependent ones. However, with the advent of deeper knowledge into this field, the abovementioned classification was found to be invalid [8,9,10]. Interestingly GLYI, though not distinguishable based on the abovementioned metal activation properties, certainly differs in terms of its distribution, localization, and abundance patterns in prokaryotes, animals, and plants.…”
Section: Introductionmentioning
confidence: 99%